Study of localized solutions of the nonlinear discrete model for dipolar BEC in an optical lattice by the homoclinic orbit method - Messikh, Azeddin; Umarov, Bakhram (Institute of Physics Publishing (UK), 2013)
We use homoclinic orbits to find solutions of a dynamical system of the dipolar Bose Einstein Condensate (BEC) in a deep optical lattice. The equation of motion is transformed to a two-dimensional map and its homoclinic orbits are computed numerically. Each homoclinic orbit leads to a different solution. These different solutions lead to different types of solitons. We also analyse the stability of the solutions.